2022
DOI: 10.3389/fmed.2022.1067162
|View full text |Cite
|
Sign up to set email alerts
|

Nordic survey on assessment and treatment of fluid overload in intensive care

Abstract: IntroductionFluid overload in patients in the intensive care unit (ICU) is associated with higher mortality. There are few randomized controlled trials to guide physicians in treating patients with fluid overload in the ICU, and no guidelines exist. We aimed to elucidate how ICU physicians from Nordic countries define, assess, and treat fluid overload in the ICU.Materials and methodsWe developed an online questionnaire with 18 questions. The questions were pre-tested and revised by specialists in intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…At present there is no gold standard for measuring fluid status. In clinical practice of ICU physicians, parameters such as fluid balance, body weight, and clinical examination are most frequently used as surrogate measures of fluid status 3,5,19 . A combination of the three parameters might be more precise compared to one parameter alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present there is no gold standard for measuring fluid status. In clinical practice of ICU physicians, parameters such as fluid balance, body weight, and clinical examination are most frequently used as surrogate measures of fluid status 3,5,19 . A combination of the three parameters might be more precise compared to one parameter alone.…”
Section: Discussionmentioning
confidence: 99%
“…Fluid overload is a well-known risk factor for mortality in critically ill patients. 1 Fluid overload in this population is often treated with loop diuretics, [2][3][4][5] but the evidence for this clinical practice is sparse. 6,7 Clinical guidelines in this field are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of treating fluid overload with diuretics is common. [31][32][33] Systematic reviews found very low and uncertain evidence for administering diuretics to patients with fluid overload in the ICU or septic shock patients. 4,5 This large international, randomised, blinded, clinical GODIF trial investigating protocolised fluid removal with furosemide versus placebo in stable adult ICU patients with moderate to severe fluid overload was designed to gain more high-quality evidence in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs are currently investigating the question further for septic shock patients (NCT05179499; NCT04569942). The practice of treating fluid overload with diuretics is common 31–33 . Systematic reviews found very low and uncertain evidence for administering diuretics to patients with fluid overload in the ICU or septic shock patients 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…This recently defined concept describes the degree to which a patient can tolerate fluid administration without causing organ dysfunction [6]. Thus, a positive fluid balance alone may not warrant reversal; its clinical impact is significant when associated with fluid overload, a condition that precedes organ dysfunction [5,7] and correlates with elevated morbidity and mortality [8][9][10][11]. Regrettably, most characterizations of fluid overload only define it arithmetically as a gain of 5-10% from admission weight without functional considerations [5,7].…”
Section: Introductionmentioning
confidence: 99%